Effects of temperature and ferric ion on the formation of glycerol core aldehydes during simulated frying. (15th August 2022) - Huang, Jianhua; Guo, Yanjun; Lin, Junyu; Xia, Tian; Wang, Lijun; Mu, Hongyan; Liu, Ruijie; Jin, Qingzhe; Song, Zhihua; Wang, Xingguo
Highlights: Four glycerol core aldehydes (GCAs) were identified in frying oil. The evolution of GCAs were well described by pseudo-first-order kinetic mode. The four GCAs lowest contents were produced at 160 °C without adding Fe 3+ . The four GCAs highest contents were formed at 180 °C with adding 0.0005 mol/L Fe 3+ . Similar changes in the saturated GCAs and unsaturated GCAs contents were occurred. Abstract: Glycerol core aldehydes (GCAs) are toxins widely formed in oils at high temperature. This study investigated the effects of frying time, temperature, and Fe 3+ content on the GCAs formation in high-oleic sunflower oil. The results showed that the GCAs (8-oxo, 9-oxo, 10-oxo-8, 11-oxo-9) concentrations increased with time following the pseudo-first-order kinetics. Frying at 160 °C without Fe 3+ and at 180 °C with 0.0005 mol·L −1 Fe 3+ yielded the lowest and highest total GCA content. The concentrations of GCAs (8-oxo) and GCAs (9-oxo) or GCAs (10-oxo-8) and GCAs (11-oxo-9) changed similarly with different frying temperature and Fe 3+ concentration. The major GCAs was GCAs (9-oxo) (40–70%), which also had the highest formation rate (5.42 × 10 −4 mg·g −1 ·h −1 ). However, GCA (10-oxo-8) and GCAs (11-oxo-9) with similar proportion (ca. 10–20%) and GCAs (8-oxo) made up the least proportions (<10%).